POLITIK HUKUM DI INDONESIA: REGULASI PERBANKAN SYARIAH DALAM TATA HUKUM INDONESIA - Alamudi, Ichwan Ahnaz (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2023)
This article is motivated by the banking sector which is undergoing dramatic changes because the concept of interest has resulted in the inability of the community in economic matters and also eventually propagated to other orders of life, including social life, politics, and other fields in a country. The presence of Islamic banking in Indonesia has had a major impact on the economy of the community, because Islamic banking is not the concept of interest. This article uses a qualitative descriptive approach that is more specific to library research data. In this paper the authors produce that the politics of law as a policy to implement the objectives of the state, especially in the field of law on the law that will run, is running and has been applied that dimbil through the values in society to achieve the goals of the state. Furthermore, the implementation of Sharia banking law is carried out in stages in the early stages of Sharia banking regulation regulated in law Number 7 of 1992 by accommodating banks in the principle of profit sharing. Sharia banking regulation in the next stage is regulated in Law No. 10 of 1998 by implementing the Sharia principle Bank model. And in the end a new law was issued Law No. 21 of 2008 which regulates Islamic banks separately from conventional banks. Keywords: Politics, Law, Islamic Banking.